1964
DOI: 10.1085/jgp.48.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation of Spike Potential in Barnacle Muscle Fibers under Low Intracellular Ca++

Abstract: Electrical properties of the muscle fiber membrane were studied in the barnacle, Balanus nubilus Darw. by using intracellular electrode techniques. A depolarization of the membrane does not usually produce an all-ornone spike potential in the normal muscle fiber even though a mechanical response is elicited. The intracellular injection of Ca++-binding agents (K 2 SO4 and K salt of EDTA solution, Ks citrate solution, etc.) renders the fiber capable of initiating all-or-none spikes. The overshoot of such a spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
1

Year Published

1967
1967
1981
1981

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(92 citation statements)
references
References 13 publications
7
84
0
1
Order By: Relevance
“…That this explanation is incomplete is shown by the fact that the Na efflux into Ca2+-free ASW was stimulated by depolarization of the membrane. Thus it may have to be supposed that the increased influx of Ca2+ during depolarization (Hagiwara & Naka, 1964) was sufficient to inhibit the transport enzyme but not to stimulate the Ca2+-dependent component of the Na efflux. It will be remembered that Bittar et al (1967) found that injection of CaCl2 into crab muscle fibres caused a transitory fall followed by a transitory rise in the Na efflux.…”
Section: Resultsmentioning
confidence: 99%
“…That this explanation is incomplete is shown by the fact that the Na efflux into Ca2+-free ASW was stimulated by depolarization of the membrane. Thus it may have to be supposed that the increased influx of Ca2+ during depolarization (Hagiwara & Naka, 1964) was sufficient to inhibit the transport enzyme but not to stimulate the Ca2+-dependent component of the Na efflux. It will be remembered that Bittar et al (1967) found that injection of CaCl2 into crab muscle fibres caused a transitory fall followed by a transitory rise in the Na efflux.…”
Section: Resultsmentioning
confidence: 99%
“…4B). The possibility of such blocking action of internal Ca was shown by Hagiwara & Naka (1964) in the barnacle muscle fibres. Injections of Ca-EGTA buffers into this tissue showed that the internal free Ca concentration should be below 8 x 1o-8 M in order to produce a Ca-dependent action potential (Hagiwara & Nakajima, 1966).…”
Section: Discussionmentioning
confidence: 96%
“…The calcium conductance attains maximum values when the intracellular concentration of Ca2+ is very low (Hagiwara & Naka, 1964;Kostyuk & Krishtal, 1977b). This was achieved in the present experiments by adding 5 mM-EGTA to the intracellular solution.…”
Section: Separation Of Two Components Of the Asymmetric Displacement mentioning
confidence: 99%